A tangible platform for mixing and remixing narratives - Sylla, Cristina Maria Santos Moreira Silva (2013)
In this article we will present a study on the social network Proedi, which included the analysis of the content of a discussion forum entitled "Technology vs Methodology", formal in its constitution, which involves a group of future teachers of a master's degree in Teaching at the University of Minho. The objective of the review was to evaluate the presence of teaching, one of the components of the Community of Inquiry Model of [1], on the basis of an analysis grid containing the categories and keywords that have been adapted by the authors of the original model. The results obtained show that the teaching presence detected in that forum resulted from the engagement and willingness to learn of the group added to the e-moderator that, throughout the discussion, was always questioning the members and instilling a critical reflection on the topic under consideration.